Death and Dying on the Social Network: An Italian Survey. Issue 3 (2nd July 2020) - Bovero, Andrea; Tosi, Chiara; Botto, Rossana; Fonti, Irene; Torta, Riccardo
Abstract: Death, bereavement, and grief are part of everyone's life experience. In the last few decades, media and social network platforms gradually began to influence people's ways of perceiving and coping with death and dying, and the research on the phenomenon of digital death is growing. Facebook is one of the most known and used social networks, and one of the few that developed specific measures to manage the profile pages of the deceased users. Based on these premises, this survey aimed to investigate how 1281 Italian participants, aged 14–77 years old, approach death on Facebook with respect to their opinions, attitudes, and emotional reactions, through an ad-hoc online survey. The results highlight how the participants seem to have different attitudes and emotions toward death, grief and mourning on the social network platform. The age of the participants seems to influence the use of the social network and the attitudes and the emotions toward the topic of investigation. Moreover, for this Italian sample, the custom of grieving and commemorating on social media is starting to spread along with the usual cultural practices without replacing them.